Venezuelan Political Thinking as Seen in the 19th – Century Newspapers - María Soledad Hernández Bencid (Ksiegarnia Akademicka Publishing, 2021)
The beginnings of Venezuelan press were inevitably linked to national political events. This medium of expression and information has become the most expeditious vehicle to convey the modernist thought. The ideas of the Enlightenment and the Encyclopedia have had positive impact positive on the Spanish American Colonies generating numerous independence movements that will shape a new political, economic, social and cultural order, thus becoming independent republics. Ideas of liberty, fraternity, equality, sovereignty, citizenship, liberalism, constitutional order, federalism, confederation, positivism, and nationalism have shaped during the Venezuelan nineteenth century a complex political‑ ideological network that gives birth to a peculiar way of thinking. Through the creation and operation of a considerable number of newspapers and magazines, these ideas were gradually consolidated and entrenched into the society and they served as a support for the changes taking place within it. The infallible work of thinkers, writers, men of letters, amateurs and politicians was worth, and since the beginning of republicanism, the country was flooded with newspapers, papers, periodicals and magazines that give life to a country and preserve intact its cultural heritage that shapes the Venezuelan political thinking of 19th century.